ECONOMIC EFFICIENCY OF PUBLIC–PRIVATE PARTNERSHIP (PPP) MECHANISMS IN THE DEVELOPMENT OF DOMESTIC TOURISM INFRASTRUCTURE - Yeshmuratova Aynur Nurjan qizi (Modern American Journals, 2025)
The development of domestic tourism is increasingly recognized as a strategic driver of regional economic growth, job creation, and cultural preservation. In this context, public–private partnership (PPP) mechanisms are viewed as a key instrument for financing, managing, and accelerating tourism infrastructure projects without overburdening the state budget. PPP enables the integration of government guarantees with private sector efficiency, allowing for large-scale investments in transport facilities, accommodation infrastructure, digital platforms, ecological tourism clusters, and heritage preservation. In countries with transitioning economies, PPP is particularly relevant due to limited fiscal resources, the need for rapid modernization, and the necessity to attract global expertise. However, the economic efficiency of PPP models depends on regulatory transparency, balanced risk allocation, long-term financial sustainability, and the capacity of local institutions to design and monitor such agreements. The tourism sector, being highly sensitive to market fluctuations and seasonal demand, requires PPP projects to be carefully structured to ensure both commercial profitability and wide socio-economic impact. This paper analyzes the role of PPP in the formation of competitive domestic tourism infrastructure and evaluates its effectiveness through indicators such as investment multiplier effects, employment generation, regional income growth, and technological innovation. Case observations from national tourism initiatives demonstrate that PPP-based projects lead not only to infrastructure improvement but also to governance innovation, community engagement, and diversification of tourism products. At the same time, challenges remain in terms of regulatory harmonization, risk predictability, and long-term maintenance obligations. The study concludes that PPP is a viable and efficient model for accelerating the development of domestic tourism infrastructure, provided that coordination mechanisms, investor incentives, and public control tools are strategically aligned with national tourism development goals.
Keywords: Public–private partnership, domestic tourism infrastructure, investment efficiency, tourism development, regional economy, infrastructure modernization, innovation, sustainable tourism, economic impact, partnership models